Afgrænsningen mellem sand og falsk skrifttolkning hos Irenæus og Grundtvig - Jacobsen, Anders-Christian (Grundtvig-studier, 1997)
The Delimitation of True and False Exegesis in Irenaeus and Grundtvig By Anders-Christian Jacobsen In the article above I examine the delimitation of true and false exegesis in Irenaeus and Grundtvig. The point of departure is a presumption that Irenaues has played a decisive role for Grundtvig’s ≫matchless discovery≪ of the importance of the Apostles’ Creed as an epitome of the content of faith, and in continuation of this as a criterion for the correct interpretation of the Bible. First I give a brief description of Irenaeus’s criticism of the Valentinians’ exegesis as it finds expression in connection with his description of the Valentinian cosmology in Adv. haer. 1,1,1. - 1,10,3. The point made by Irenaeus here is that the tradition of the church as it is summed up in ≫regula veritatis≪, is the criterion for what is true and what is false exegesis. Then follows a lengthy description of Grundtvig’s ≫matchless discovery≪ of the Creed and Irenaeus’s importance in that connection. First I point out that Grundtvig’s ≫matchless discovery≪ was the culmination of a long struggle against Rationalist theology and in particular against the exegesis of the Rationalist theologians. This discussion is based on a reading of Grundtvig’s memoirs about the period till (and including) the ≫matchless discovery≪ and of selected Grundtvig writings from that period. The study of these texts confirms that ever since his boyhood Grundtvig saw Rationalist theology and especially its Biblical criticism as a challenge. At the beginning of the 1820s, however, he has not yet found a tenable answer to the challenge. Some confession-like statements in the sermons from the beginning of the 1820s may, however be seen as expressing an incipient understanding of the importance of the Creed as an epitome of the content of the faith. It is only with the ≫matchless discovery≪ of the importance of the Creed in 1825, however, that he arrives at a genuine breakthrough. Next, on the basis of the Preface to ≫ The Rejoinder of the Church≪, I argue that the suddenly matured recognition of the significance of the Creed in July 1825 does not only mean that Grundtvig replaces the Holy Scripture as a foundation of faith with the Creed, but that the Creed comes to function as a norm for exegesis. Finally I establish it as probable, on the basis of both the Preface to The Rejoinder of the Church and a yet unpublished Grundtvig text that Irenaeus came to play a considerable role as a norm for exegesis. Thus, in the Rejoinder of the Church, an explicit reference to Irenaus is found as having inspired the confrontation with H.N. Clausen which, to a large extent was a conflict about exegesis. Moreover, the preface to ≫ The Rejoinder of the Church≪ is dated ≫ Ireneai Day 1825≪. These references to Irenaeus as the originator of the new view of the Creed as a norm for exegesis are supported by the fact that Grundtvig’s sermons from 1923 and the following years bear evidence of a relatively powerful influence from Irenaeus and the fact that, probably a short time before his ≫matchless discovery≪, Grundtvig has written out extracts and summeries of pericopes from Adv.haer. that are central to this question. Thus I find it well documented that Ireneaus was a decisive source of inspiration for Grundtvig’s discovery of the Creed as a criterion for exegesis.